Study on characteristics of mooring system of a new floating offshore wind turbine in shallow water by experiment - Huo, Fali; Xu, Jie; Yang, Hongkun; Yuan, Zhaojun; Shen, Zhongxiang (Frontiers in Energy Research, 2023)
At present, researches on floating offshore wind turbine are mainly focused on deep water areas beyond 50 m, and less research has been conducted for shallow water. Considering that the floating fan still has many application values in 30 m–50 m area, it is necessary to study the floating offshore wind turbine in shallow water area. With the shallow design water depth and the effect of topography, the environmental condition is complex. Therefore, it is relatively difficult to design the mooring system. In this paper, a multi-point mooring system is proposed which based on PivotBuoy, a floating offshore wind turbine designed by X1-Wind Company. The characteristics of motion responses of the floating offshore wind turbine and mooring force under different mooring cable schemes are studied by physical model experiment. Through these results, it can be found that when the mooring system adopts the hybrid mooring cable scheme (anchor chain + polymer cable + anchor chain), the pitch and heave motion responses of the floating offshore wind turbine will increase by about 30% maximally, the mooring cable tension will decrease by about 27%. This paper also studies the influence of water depth and mooring cable pretension on the mooring system under the hybrid mooring cable scheme, and the characteristics of mooring system in 22.5 m shallow water. These results can provide certain theoretical guidance for the design of mooring system of floating offshore wind turbine in shallow water.